Substitution of corn meal with dry brewer’s yeast in the diet of sheep - Oliveira, Ronaldo L; Oliveira, Robson J F; Bezerra, Leilson R; Nascimento, Thiago V C; de Pellegrini, Caius B; de Freitas Neto, Marcondes D; do Nascimento Júnior, Nilton G; de Souza, Wender F (Revista Colombiana de Ciencias Pecuarias, 2016)
dry brewery residue can be an important tool for reducing the cost of concentrated feed for sheep. Objective: to evaluate the intake, digestibility and feeding behavior of sheep fed dry brewery residue. Methods: twenty lambs of undefined breed, with 30.33 ± 4.94 Kg body weight and seven months average age were used. Animals were fed diets containing 50% forage (Tifton-85 hay) and 50% concentrate. Treatments consisted of 0, 33, 66, and 100% corn meal substitution with dry brewery residue. Data were subjected to analysis of variance and regression analyses using a 5% significance level. Results: dry matter intake based on average body weight was 3.40% and showed no significant variation with the substitution level. Diet composition did not affect (p > 0.05) intake of crude protein, ether extract, ash, lignin and total digestible nutrients (71.26%). Substitution of corn meal with dry brewery residue did not affect nutrient digestibility (p > 0.05). Feeding behavior, time spent feeding and ruminating were not affected (p > 0.05) by the substitution; however, idling time was quadratically related to the percentage of dry brewery residue that was substituted for corn meal, with an inflection point at 41.58% replacement. Conclusion: dry brewery residue can replace up to 100% corn meal without negative effects on intake, digestibility or the feeding behavior of sheep.